Measurement of Serum Klotho in Systemic Sclerosis. (22nd August 2017) - Talotta, Rossella; Bongiovanni, Sara; Letizia, Teresa; Rigamonti, Federica; Ditto, Maria Chiara; Atzeni, Fabiola; Salaffi, Fausto; Batticciotto, Alberto; Gerardi, Maria Chiara; Antivalle, Marco; Vago, Tarcisio; Benucci, Maurizio; et al.
Abstract : Background . The aim of our study was to evaluate the serum concentration of klotho in a cohort of systemic sclerosis (SSc) patients compared to that of healthy controls and to correlate its levels with the degree and the kind of organ involvement. Methods . Blood samples obtained from both patients and controls were collected and analysed by an ELISA test for the determination of human soluble klotho. Scleroderma patients were evaluated for disease activity through clinical, laboratory, and instrumental assessment. Results . Our cohort consisted of 81 SSc patients (74 females, mean age 63.9 ± 13.1 years) and 136 healthy controls (78 females, mean age 50.5 ± 10.7 years). When matched for age, serum klotho concentration significantly differed between controls and patients (p < 0.001 ). However, in SSc patients, we did not find any significant association between serum klotho and clinical, laboratory, and instrumental findings. Lower serum levels of klotho were detected in 4 patients who were anticitrullinated peptide antibody (ACPA) positive (p = 0.005 ). Conclusions . Our data show a lower concentration of klotho in the serum of SSc patients compared to that of healthy controls, without any significant association with clinical manifestations and laboratory and instrumental findings. The association between serum klotho and ACPA positivity requires further investigation.